Kemiskinan Dalam Perspektif Struktural Fungsional - Rosana, Ellya (Universitas Islam Negeri Raden Intan Lampung, 2019)
Poverty is a person's inability to meet their needs caused by the scarcity of tools to meet daily needs, education, and inadequate employment to meet the needs of life. Efforts are being made to reduce poverty increasingly diverse but poverty is indeed difficult to be eliminated, but at least it can be minimized. Adherents of functional structural theory assume that poverty is functional (has a function) on social systems in society. The poor function to do